A WiMAX circularly polarized antenna array using slot‐coupling feeding technique. Issue 7 (26th April 2016) - Zhang, Y.‐Q.; Shang, F.
ABSTRACT: In this letter, we present a circular polarization antenna array using the novel slot‐coupling feeding technique. This antenna includes eight elements which are installed in line, each array element is fed by means of two microstrip lines with equal amplitude and phase rotation of 90°. The feeding microstrip lines are coupled to a square patch through a square‐ring slot realized in the feeding network ground plane. With the presence of the slots, this antenna array is able to cover the range of frequency of 3 GHz to 4 GHz. The size of the proposed antenna array is 7 λ × 1.8 λ × 0.4 λ . The measured gain is 15.2 dBi and the bandwidth of S 11< −10 dB is 1 GHz (3–4 GHz, 28%). The antenna array is suited for the WiMAX applications. With the use of slot‐coupling feeding technique, the measured bandwidth for axial ratio < 3 dB is about 24% in the WiMAX frequency band (3.3–3.8GHz). The measured HPBW of the y – z planes is larger than 62°. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:567–574, 2016.